Projected time to elimination of cervical cancer in the USA: a comparative modelling study. (April 2020) - Burger, Emily A; Smith, Megan A; Killen, James; Sy, Stephen; Simms, Kate T; Canfell, Karen; Kim, Jane J
Summary: Background: In May, 2018, the Director-General of WHO issued a global call to eliminate cervical cancer as a public health problem, which will involve ambitious screening and vaccination coverage targets. We aimed to assess the potential for, and timing of, cervical cancer elimination in the USA and whether this could be expedited by adopting ambitious coverage targets, using two cervical cancer simulation models. Methods: In this modelling study, we used two independently-developed cervical cancer microsimulation models—Harvard and Policy1-Cervix—to estimate changes in the incidence of human papillomavirus (HPV)-induced cervical cancer over time in the USA, including herd effects from vaccination. We compared nine alternative scenarios for prophylactic HPV vaccination and cervical screening scale-up with a status quo scenario that involved no additional interventions in the context of a threshold for cervical cancer elimination of four or fewer cases per 100 000 women-years. We also estimated the number of cervical cancer cases that could be averted between 2019 and 2100 associated with the adoption of ambitious goals for cervical cancer screening and vaccination coverage, and other potential strategies. Findings: Under status quo assumptions, the Havard and Policy1-Cervix models projected that cervical cancer incidence would decrease to less than four or fewer new cases per 100 000 women-years by the 2038 and 2046, respectively. Scaling up screening coverage to 90% in 2020, was the most effective intervention to expedite time to elimination (10–13-year reduction), averting a mean of 1400–2088 additional cases annually between 2019 and 2100. Increasing HPV vaccination coverage to 90% or vaccinating adults aged 26–45 years had relatively little effect on cervical cancer incidence. Sensitivity analysis using different population structures resulted in differences in time to elimination (range −10 years to +27 years) compared with status quo predictions. Interpretation: The USA is on track to eliminate cervical cancer as a public health problem in the next two to three decades. Time to elimination could be expedited by 10–13 years by achieving higher screening coverage. Targeting of underscreened and under-vaccinated women remains key to achieving cervical cancer elimination for all women. Funding: US National Cancer Institute.